A highly selective fluorescent probe for direct detection and isolation of mouse embryonic stem cells. Issue 21 (1st November 2015) - Chandran, Yogeswari; Kang, Nam-Young; Park, Sung-Jin; Husen Alamudi, Samira; Kim, Jun-Young; Sahu, Srikanta; Su, Dongdong; Lee, Jungyeol; Vendrell, Marc; Chang, Young-Tae
Graphical abstract